Impact of Information Security Policies Compliance (ISPC) on Reducing the Incidence of Security Breaches in Organizations: Systematic Literature Review - Mohamud, Abdulkadir Jeilani; T.K.A, Rahman (2024)
Information security policy compliance plays an important role in reducing the incidence of security breaches in organizations. Recently, information security practices in firms have been widely examined. Therefore, inadequate efforts have been made to assess and systematically review the present study status to offer insights into prior study findings. This systematic literature review investigated the impact of ISPC on reducing the incidence of security breaches in organizations. After inclusion and exclusion criteria process conducted, 42 research publications from Google scholar, Sage, IEEE, ACM, ScienceDirect, Springer, Jstor, Wiley, Taylor & Francis databases (2009 – 2024) included, most of the studies utilized quantitative research methods to explore factors influencing compliance with information security policies, such as employee demographics, organizational strategies, and deterrence mechanisms, A few studies adopted qualitative methods to assess the effectiveness of security programs or to propose measures to enhance compliance. The findings suggested that not only information security policy compliance reduce incidences of security breaches in organizations but also other factors such as employee training, awareness, management support, regular audits, and the integration of advanced security technologies are identified as crucial for reducing security breaches. The implications of these findings for organizational practices and future research directions are discussed, providing valuable insights for policymakers, IT professionals, and researchers aiming to strengthen information security frameworks and reduce the incidence of security breaches.